penerapan model latihan drill for game like situation untuk meningkatkan kemampuan servis atas bolavoli klub activa lintau - bonnie aditya effendy; Muhamad Sazeli Rifki; Arif Fadhli Muchlis (Jurusan Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2018)
The problem in this study was the low service ability of the Activa Lintau club volleyball. The problem is likely due to lack of proper training methods used by trainers. This study aims to reveal the effect of the application of the Drills For Game-Like Situation Exercise method to improve the ability to service the volleyball club Activa Lintau. This type of research is a quasi experiment. The population in this study is the male volleyball athlete who joined the Activa Lintau club as many as 20 people athletes whose age range 17 years to 25 years. The sampling technique was used with total sampling technique, with the number of samples used as many as 20 people. Data were collected by performing top service precision tests with ten repetitions. Data were analyzed using t-test or mean difference test. The results of the research and data analysis show that the Drills For Game-Like Situation training method has a significant influence on the service capability of the Activa Lintau club bolavoli. Based on the results of data analysis, found t count = 72.97> ttable = 1.792 with the average increase is 8.